Asymmetric sulfone polymer hollow ultrafiltration membrane as well as preparation method and application thereof
By designing an asymmetric structure and auxiliary interception zone in the hollow ultrafiltration membrane of sulfone polymers, the contradiction between flux and interception efficiency in the prior art is solved, and an efficient clarification of ultrafiltration effect is achieved.
Patent Information
- Application Number
- CN202411926619.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
While the existing sulfone polymer clarified ultrafiltration membranes improve the retention efficiency, they lead to a sharp drop in flux, which cannot meet the needs of practical applications.
Asymmetric sulfone polymer hollow ultrafiltration membrane is used, and the first hole diameter on its first surface is within a reasonable range. By regulating the average pore size structure of the membrane main body is a gradient pore size, there are non-directional tortuous passages and auxiliary interceptor areas, and the porosity and pore size ratio are optimized to achieve both high interceptibility efficiency and flux.
A good overall membrane retention efficiency, flux and target substance yield are achieved, avoiding the problem of too low flux and improving filtration efficiency.
Smart Images

Figure CN119733388A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane materials, and more particularly to an asymmetric sulfone polymer hollow ultrafiltration membrane and a preparation method and application thereof. Background Art
[0002] As a membrane separation technology, biological ultrafiltration performs separation based on molecular size and is mainly used to separate macromolecular substances such as proteins, polysaccharides, and nucleic acids. Clarifying ultrafiltration, as a type of biological ultrafiltration, mainly refers to the use of ultrafiltration membrane separation technology to achieve the clarification process of the solution. In clarifying ultrafiltration, the solution passes through the ultrafiltration membrane, where small molecules and solvents can pass through the membrane pores, while macromolecular solutes are retained by the membrane, thereby achieving the separation or concentration of solutes of different molecular weights in the solution. Sulfone polymers have become one of the first choices for clarifying ultrafiltration membrane raw materials due to their advantages such as high temperature resistance and biocompatibility.
[0003] At present, most of the sulfone polymer clarification ultrafiltration membranes on the market have a relatively dense inner surface (which means that the pore size of the membrane on the inner surface is very small and the pore area ratio is very small), and the pore size of the membrane tends to increase from the inner surface to the outer surface. Such a membrane structure is conducive to the corresponding substances being fully retained on the inner surface, while the filtration resistance is small and the flux is high, thereby achieving both clarification ultrafiltration retention efficiency and flux. For example, U.S. Patent No. US5886059A (applied by Parr Corporation) - Highly asymmetric polyethersulfone filtration membranes discloses a highly asymmetric polymer membrane, which is prepared from a polyethersulfone polymer and has a highly asymmetric region with gradually increasing pore size. One side of the membrane is a skin surface with relatively small diameter pores (i.e., the first surface of the present invention, which refers to the liquid inlet surface in clarifying ultrafiltration), and the other side of the membrane has relatively large diameter pores (i.e., the second surface of the present invention, which refers to the liquid inlet surface in clarifying ultrafiltration). The polymer membrane has an average flow pore size of about 0.05 μm to about 2 μm, has a good flux, and is suitable for use in clarifying filtration.
[0004] However, with the increasing number of applications of clarifying ultrafiltration membranes for collecting target substances through membrane pores (for example, in the production process of insulin, there will be high molecular weight proteins or other macromolecules that may affect the purity and safety of insulin, and clarifying ultrafiltration is the preferred filtration method for removing such high molecular weight proteins or other macromolecules in insulin raw materials (the target substance enters the second surface through the membrane pores for collection, while the removed substance is retained on the first surface)), people have higher and higher requirements for the retention efficiency of clarifying filtration, and reducing the pore size of the first surface of the membrane (i.e., the liquid inlet surface) is the most direct and effective way to improve the retention efficiency. However, this method will lead to a sharp attenuation of the overall flux of the membrane, and then the membrane flux is too low, affecting the filtration efficiency and increasing the cost. Therefore, developing a sulfone polymer ultrafiltration membrane that can both improve the membrane retention efficiency and have less effect on the flux is a problem that researchers have always wanted to solve. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an asymmetric sulfone polymer hollow ultrafiltration membrane and a preparation method and application thereof, wherein the pore size of the first hole on the first surface of the ultrafiltration membrane is within a reasonable range, and the average pore size of the ultrafiltration membrane body is adjusted to first increase, then decrease, and then increase again, and the membrane is a gradient pore size membrane, has a non-directional tortuous passage in the body, has a suitable ratio of the pore size of the auxiliary retention zone to the pore size of the first hole, a suitable average distance from the auxiliary retention zone to the first surface, and the membrane has a structure with a suitable porosity, so as to achieve good overall membrane retention efficiency, overall membrane flux and yield of the target substance.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: an asymmetric sulfone polymer hollow ultrafiltration membrane, comprising a main body, one side of the main body is a first surface facing the inner cavity, the other side of the main body is a second surface, the main body has a non-directional tortuous passage, the first surface contains a plurality of first holes, the SEM average pore size of the first holes is 1nm-450nm; the ultrafiltration membrane is a gradient pore size membrane, and in the thickness direction from the first surface to the second surface, the average pore size of the main body first increases, then decreases, and then increases; the main body includes an auxiliary retention area, the nearest average distance A from the auxiliary retention area to the first surface is not less than 40μm; the ratio of the SEM average pore size of the auxiliary retention area to the SEM average pore size of the first holes is 1.5-10, and the overall porosity of the ultrafiltration membrane is 30%-75%.
[0007] The ultrafiltration membrane of the present invention is prepared from sulfone polymers, which have the advantages of excellent mechanical properties, thermal stability, biocompatibility, easy phase separation and pore formation, etc. In the existing internal pressure ultrafiltration membranes used for clarification, the first surface (i.e., the inner surface) and the vicinity thereof are regions with smaller pore diameters in the membrane, while the second surface (i.e., the outer surface) is an open large pore, and most of the impurities to be trapped are trapped on the first surface and its vicinity; in order to improve the interception efficiency of the membrane for the corresponding impurities, those skilled in the art generally reduce the pore diameter of the first surface (i.e., the inner surface), but as the pore diameter of the first surface continues to decrease, the overall flux of the membrane drops sharply, resulting in an overall flux of the membrane that is too low and cannot meet the needs of practical applications. The inventors of the present invention have discovered through continuous research that the pore size of the first holes on the first surface of the ultrafiltration membrane is within a suitable range, that is, the SEM average pore size of the first holes is controlled within the range of 1nm-450nm. After the first surface effectively retains the impurities to be retained, there is no need to further reduce the pore size value of the first holes. The impurities to be retained can be further retained by the auxiliary retention area inside the membrane body, thereby improving the overall retention efficiency of the membrane. The auxiliary retention zone is located in the "decrease and then increase" transition zone where the average pore size in the thickness direction from the first surface to the second surface of the membrane body first increases, then decreases, and then increases. Admittedly, the SEM average pore size of the auxiliary retention zone cannot be too large, because if the SEM average pore size of the auxiliary retention zone is too large, it will not be able to meet the further retention of related impurities, but the SEM average pore size of the auxiliary retention zone cannot be too small, otherwise it will also cause a sharp drop in the overall flux of the membrane and then cause the overall flux of the membrane to be too low; after research, we hope that the SEM average pore size of the auxiliary retention zone is slightly larger than the SEM average pore size of the first hole, and adjust the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole. The pore size ratio is 1.5-10; at the same time, the ultrafiltration membrane body of the present invention has a non-directional tortuous passage and the ultrafiltration membrane is a gradient pore size membrane, so that the membrane pores inside the membrane partially overlap in the direction from the first surface to the second surface. In particular, the holes in the overlapping part of the auxiliary retention zone play a key role in the retention of related impurities. At the same time, the farther the distance from the auxiliary retention zone to the first surface is, the fluid still has a certain distance to enter the auxiliary retention zone through the first hole on the first surface. Therefore, the number of overlapping membrane pores in the auxiliary retention zone is relatively large, which can play a better auxiliary retention role. If the auxiliary retention zone is close to the first surface, the number of overlapping holes will be too small, and it cannot play a good auxiliary retention role. Therefore, by regulating the pores in the auxiliary retention zone to have a suitable pore size, and at the same time, under the synergistic effect of the non-directional tortuous passage in the main body, the nearest average distance A from the auxiliary retention zone to the first surface is not less than 40 μm (longer distance), the ratio of the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole is 1.5-10, and the ultrafiltration membrane is a gradient pore size membrane, it can further effectively retain related impurities and thereby improve the retention efficiency.
[0008] Since the SEM average pore size of the auxiliary interception zone is slightly larger than the SEM average pore size of the first hole, the effect on the flux of the entire membrane is relatively small. At the same time, under the synergistic effect of the overall porosity of the membrane being 30%-75% (i.e., the membrane as a whole has more holes), the membrane as a whole still has a good flux. Therefore, the SEM average pore size of the first hole on the first surface, the ratio of the SEM average pore size of the auxiliary interception zone to the SEM average pore size of the first hole, the non-directional tortuous path in the body, the nearest average distance from the auxiliary interception zone to the first surface, the porosity of the entire membrane are all within a reasonable range, and the ultrafiltration membrane is a gradient pore size membrane, and the obtained ultrafiltration membrane has a good interception efficiency and a good overall membrane flux.
[0009] Because the average pore size of the ultrafiltration membrane body first increases, then decreases, and then increases again, and the ultrafiltration membrane is a gradient pore size membrane, that is, the pore size of the membrane pores in the membrane body structure changes gradually, that is, there is no area with particularly large membrane pores. Under this specific membrane structure, the flow rate of the fluid will change to a certain extent with the change of the pore size in the membrane body, which is beneficial to increase the turbulence on the first surface of the membrane so that the related impurities trapped on the first surface are more easily carried away by the passing fluid (no need to create turbulence through external force, which can reduce damage to the target substance), prevent excessive impurities from accumulating on the first surface and clogging the membrane pores, and at the same time reduce concentration polarization and improve interception efficiency; at the same time, the flow rate of the fluid will not change suddenly inside the membrane, and will not cause damage to the target substance (such as protein, etc.), and it is also beneficial to protect the internal structure of the membrane from being destroyed, so that the membrane as a whole has a stable flux, and the internal structure of the membrane pore controls the change of the fluid flow rate so that the damage to the target substance is extremely low, with a good target substance yield, and an unexpected technical effect (usually, only when the fluid flow rate changes greatly will it bring a turbulent effect to the fluid on the first surface). At the same time, under the synergistic effect of the nearest average distance between the auxiliary interception zone and the first surface being not less than 40 μm and the ratio of the SEM average pore size of the auxiliary interception zone to the SEM average pore size of the first hole, it further means that the pore size change from the first surface to the auxiliary interception zone is very gentle, and the flow rate change is relatively small when the fluid flows from the first surface to the auxiliary interception zone, which can further protect the fibers in the auxiliary interception zone from being damaged by a large change in flow rate, so that the membrane as a whole has a stable interception efficiency and flux. Therefore, under the effect that the average pore size of the ultrafiltration membrane body first increases, then decreases, and then increases again, the ultrafiltration membrane is a gradient pore size membrane, the nearest average distance between the auxiliary interception zone and the first surface is not less than 40 μm, and the ratio of the SEM average pore size of the auxiliary interception zone to the SEM average pore size of the first hole is within a specific range, the prepared ultrafiltration membrane has a stable flux and interception efficiency and a good target substance yield.
[0010] In summary, the inventors of the present application have achieved excellent and stable retention efficiency even when the pore size of the first holes on the first surface is relatively larger, the membrane still has a good overall flux, the membrane has a stable flux, and at the same time the yield of the target substance is high, by regulating the ratio of the SEM average pore size of the auxiliary retention zone of the membrane to the SEM average pore size of the first holes, the non-directional tortuous passage in the main body, the nearest average distance from the auxiliary retention zone to the first surface, the overall porosity of the membrane, the average pore size of the main body in the thickness direction from the first surface to the second surface first increases, then decreases, and then increases again, and the ultrafiltration membrane is a gradient pore size membrane, which has unexpected technical effects.
[0011] During the membrane preparation process, in the direction perpendicular to the membrane thickness (if the membrane is in the form of a flat membrane, this direction is the planar direction; if the membrane is in the form of a hollow fiber membrane, this direction is perpendicular to the radial direction), its various characteristics such as the pore size are roughly uniform and basically consistent, so the pore size of the entire plane can be reflected by the pore size of a partial area on the corresponding plane. The auxiliary interception zone is located in the transition zone of "decrease and then increase" in which the average pore size of the main body increases first, then decreases, and then increases in the thickness direction from the first surface to the second surface of the membrane pore body. The position of the auxiliary interception zone is determined in the present invention by using a scanning electron microscope to characterize the cross-section of the entire membrane, for example, obtaining a scanning electron microscope image of the membrane cross-section with a magnification of 500 or 600 or 700 or 800 or 1000, determining the transition zone S of the pore size "decrease and then increase", and then continuously photographing the region S, for example, obtaining multiple membrane cross-section electron microscope images with a magnification of 10000 or 20000 or 50000, and measuring the pore size of the membrane cross-section electron microscope images obtained at multiple magnifications of the region S, by selecting multiple holes on the same plane to measure their SEM pore size, and calculating S The plane with the obtained SEM minimum pore size value is the minimum pore size plane of the auxiliary retention zone of the membrane. Then, the membrane cross section from the plane with the minimum pore size to the second surface is continuously photographed to obtain multiple membrane cross-section electron microscope images with a magnification of 10000, 20000 or 50000. Then, the SEM average pore size of the corresponding plane is gradually measured from the plane with the minimum pore size toward the second surface by the same method, until the SEM average pore size value is 1.5 times the SEM minimum pore size value of the auxiliary retention zone of the membrane. The plane with the SEM average pore size is determined as the interface P1 of the auxiliary retention zone of the membrane close to the second surface. The same method is used to determine the interface P2 of the auxiliary retention zone of the membrane close to the first surface. The area between the interface P1 and the interface P2 is called the auxiliary retention zone. The average value of the distance between the interface P2 and the first surface is the nearest average distance A from the auxiliary interception zone to the first surface, and the average value of the distance between the interface P1 and the interface P2 is the thickness of the auxiliary interception zone. The method for measuring the nearest average distance A and the thickness of the auxiliary interception zone is to measure the distance from the interface P2 to the first surface and the distance between the interface P1 and the interface P2 of multiple auxiliary interception zones on the cross-sectional SEM image of the membrane by computer software (such as Matlab, NIS-Elements, etc.) or manually, and calculate the average value of each. Correspondingly, the SEM average pore size of the auxiliary interception zone is obtained by uniformly selecting points (preferably more than 10 points) at different positions as measurement objects after the area between the interface P1 and the interface P2 is characterized by a scanning electron microscope at a certain magnification, such as 5000 times, 10000 times or 20000 times, and then using corresponding computer software (such as Matlab, NIS-Elements, etc.) or manually to measure the corresponding SEM pore size, and then calculating the average value to obtain the SEM average pore size of the auxiliary interception zone.
[0012] The SEM average pore size of the first pores of the ultrafiltration membrane can be characterized by first using a microscope to characterize the first surface of the membrane (for the first surface of the hollow fiber membrane, the magnification can be clearly confirmed as many pores as possible, such as 5000 times, 10000 times, 20000 times, etc.), and the corresponding SEM image is obtained. The pores formed on the first surface are circular, elliptical or nearly elliptical in shape. Since the pore size of the pores on the first surface of the membrane is roughly uniform, a certain area, such as 400 μm, is selected. 2 (20 μm times 20 μm), 225 μm 2 (15 μm x 15 μm), 100 μm 2 (10 μm times 10 μm), 1 μm 2 (1 μm multiplied by 1 μm), the specific area size depends on the actual situation, and then the corresponding computer software (such as Matlab, NIS-Elements, etc.) or manual measurement is used to measure the longest line segment of the two-point line segments on the periphery of the connecting hole as the major diameter, and then the longest line segment of the line segments connecting the two points on the periphery of the hole perpendicular to the major diameter is measured as the first hole SEM average pore size, and several tests are performed (preferably more than 10 times, the specific number of times depends on the situation), and the average value is calculated as the SEM average pore size of the first hole described in the present invention. Of course, those skilled in the art can also obtain the above parameters by other measurement methods, and the above measurement methods are for reference only.
[0013] The gradient pore size membrane refers to an ultrafiltration membrane whose overall pore size changes gradually, and the rate of change of the pore size is relatively small, that is, there will be no area with a very large pore size, that is, there will be no cracks in the scanning electron microscope (SEM) image at a magnification of 60×. For example, a crack can be observed in the scanning electron microscope image of the entire membrane at a magnification of 60× in the hollow fiber membrane prepared in Example 1 of patent CN114452844A.
[0014] The non-directional tortuous pathways of the present invention refer to randomly oriented groove structures and / or discretely distributed hole structures, and each non-directional tortuous pathway is interconnected.
[0015] The several holes refer to 2 or more holes.
[0016] Commonly used testing methods for porosity include mercury injection method, density method and dry and wet film weighing method, etc. Of course, those skilled in the art can also obtain the above parameters through other testing methods. The above testing methods are for reference only.
[0017] As a further improvement of the present invention, the SEM average pore size of the auxiliary interception zone is 10 nm-500 nm; and the average closest distance A from the auxiliary interception zone to the first surface is 50 μm-180 μm.
[0018] The auxiliary interception zone in the membrane body can intercept substances that are not successfully intercepted by the first surface again to improve the interception efficiency. In the present invention, the SEM average pore size of the auxiliary interception zone is controlled to be 10nm-500nm. Such pore size makes the partially overlapping holes in the auxiliary interception zone beneficial to further interception of related impurities under the action of the tortuous path. At the same time, the average distance A from the auxiliary interception zone to the first surface is 50μm-180μm, preferably 60μm-170μm, more preferably 70μm-160μm, further preferably 80μm-150μm, and most preferably 85 μm-140μm, that is, the distance from the auxiliary retention zone to the first surface is far, and the fluid containing impurities entering the membrane enters the auxiliary retention zone through a relatively long path. Relatively speaking, the farther the distance from the first surface, the more overlapping holes appear in the auxiliary retention zone, and the more holes can intercept impurities, with better interception efficiency; at the same time, the holes in the auxiliary retention zone have a suitable pore size, that is, the SEM average pore size of the first holes relative to the first surface is larger, which can reduce the influence of the existence of the auxiliary retention zone on the flux, so that the membrane as a whole still has a higher flux.
[0019] As a further improvement of the present invention, the pore area ratio of the first surface is 2%-30%, and the initial water contact angle is 50°-85°.
[0020] The hydrophilicity of the ultrafiltration membrane greatly affects the yield of protein substances. Generally, the better the hydrophilicity of the membrane, the higher the yield of the protein product. Therefore, in the present invention, the ultrafiltration membrane needs to be relatively hydrophilic. After continuous research, it was found that the initial water contact angle of the first surface of the ultrafiltration membrane is regulated to 50°-85°, which has good hydrophilicity, which is beneficial for the target substance to pass through the membrane pores on the first surface and enter the membrane filaments. However, we do not want the first surface to be too hydrophilic, because in order to make the first surface of the membrane quite hydrophilic, the membrane needs to be hydrophilically modified. The commonly used method for hydrophilic modification is to add hydrophilic modifiers. When these hydrophilic modifiers are in large amounts, they are relatively easy to dissolve during ultrafiltration. On the one hand, it pollutes the filtered fluid, and on the other hand, it is easy to cause clogging of the membrane pores, lower membrane flux, and shorter membrane service life.
[0021] Since the ultrafiltration membrane of the present invention is an internal pressure filtration, on the basis of the first surface of the membrane having a suitable contact angle, the pore area ratio of the first surface is adjusted, that is, the number of first holes on the first surface is controlled on the basis of the first holes having a suitable pore size on the first surface. It is found through research that if the pore area ratio of the first surface is too small, the flux of the entire membrane will decrease sharply, resulting in a low overall flux of the membrane. However, if the pore area ratio of the first surface is too large, the compressive strength of the first holes on the first surface will be too low, and the first holes are prone to collapse or deformation during the filtration process, thereby affecting the stability of the membrane flux and the stability of the interception efficiency. Therefore, the pore area ratio of the first surface is adjusted to 2%-30%. On the one hand, the relatively efficient interception efficiency of the first surface is guaranteed, and on the other hand, the flux of the entire membrane will not be too low. At the same time, the first surface can be guaranteed to have a good compressive strength during filtration. Even during long-term internal pressure filtration, the integrity and stability of the first holes on the first surface can be guaranteed, and collapse or deformation are not easy to occur, so that the entire membrane has a stable flux.
[0022] The initial water contact angle is tested using a contact angle tester with water as the test liquid. A regular contact angle is formed at the moment (usually within 0.4s) when 10-100 microliters of water are evenly dropped onto the first surface of the ultrafiltration membrane. Of course, those skilled in the art can also obtain the above parameters through other testing methods. The above testing methods are for reference only.
[0023] The pore area ratio of the first surface is the ratio of the sum of the pore areas on the first surface to the area of the first surface. The first surface of the membrane can be characterized by an electron microscope to obtain a corresponding SEM image. Since the pores on the first surface of the membrane are roughly uniform, a certain area can be selected, such as 1 μm 2 (1μm times 1μm) or 9μm 2 (3μm times 3μm) or 25μm 2 (5μm times 5μm) or 100μm 2 (10μm times 10μm) or 400μm 2 (20 μm multiplied by 20 μm), the specific area size depends on the actual situation, and then the apertures of all holes in the area are measured by corresponding computer software or manually, and then the areas of the holes in the area are calculated, and the hole area in the area is obtained by summing them up, and then divided by the selected part area to obtain the hole area rate of the first surface. Of course, those skilled in the art can also obtain the above parameters by other testing methods, and the above testing methods are for reference only.
[0024] As a further improvement of the present invention, the thickness of the auxiliary retention zone is 3μm-20μm; and / or, the thickness of the auxiliary retention zone is 3%-15% of the overall thickness of the membrane; and / or, the nearest average distance B from the auxiliary retention zone to the second surface is not higher than 15μm.
[0025] We adjust the thickness of the auxiliary retention zone to 3μm-20μm. The auxiliary retention zone with this thickness can meet the purpose of further improving the retention efficiency and at the same time have a suitable dirt-receiving space so that the membrane pores in the auxiliary retention zone are not easily clogged. If the thickness of the auxiliary retention zone is too thick, although it can better meet the retention, its flux will be slightly lower. Similarly, if the thickness of the auxiliary retention zone is too thin, it will have little effect on further improving the retention efficiency. Furthermore, by adjusting the thickness of the auxiliary retention zone to be 3%-15% of the overall thickness of the membrane, that is, the thickness of the auxiliary retention zone is thinner than the overall thickness of the membrane, although the SEM average pore size of the auxiliary retention zone is smaller than the overall SEM average pore size of the membrane, because the thickness of the auxiliary retention zone is thinner than the overall thickness of the membrane, it has little effect on the overall flux of the membrane. Under the condition that the thickness of the auxiliary retention zone is 3%-15% of the overall thickness of the membrane, it has excellent flux.
[0026] Furthermore, since the thickness of the auxiliary retention zone is within a reasonable range and the thickness of the auxiliary retention zone accounts for a relatively small proportion of the overall thickness of the membrane, it is further hoped that the distance from the auxiliary retention zone to the second surface is relatively close, that is, the distance from the interface P1 of the auxiliary retention zone to the second surface is relatively small. After research, the nearest average distance B from the auxiliary retention zone to the second surface (i.e., the outer surface) is preferably not higher than 15 μm, so that the auxiliary retention zone can provide certain support to the second surface, so that it can have excellent compressive strength during filtration, and the membrane pores on the second surface and its vicinity are not easily deformed and collapsed, and have a stable overall membrane flux. If the nearest average distance B from the auxiliary retention zone to the second surface is too large, the supporting effect on the second surface is relatively small, and it cannot play a role in improving the compressive strength of the second surface. Therefore, we adjust the thickness of the auxiliary retention zone to 3μm-20μm, the thickness of the auxiliary retention zone is 3%-15% of the overall thickness of the membrane, and the average distance B from the auxiliary retention zone to the second surface is not higher than 15μm. That is, the auxiliary retention zone has a suitable position and thickness. The ultrafiltration membrane we obtained has better retention efficiency, more stability and better overall membrane flux.
[0027] The nearest average distance B from the auxiliary retention zone to the second surface is the average distance between the interface P1 of the auxiliary retention zone of the membrane close to the second surface and the second surface. Its specific measurement method is the same as the measurement method of the nearest average distance A from the interface P2 of the auxiliary retention zone to the first surface.
[0028] As a further improvement of the present invention, the auxiliary interception zone also includes interception fibers that form a porous structure of the auxiliary interception zone, and the SEM average diameter of the interception fibers is 30nm-90nm; the overall porosity of the ultrafiltration membrane is 35%-70%.
[0029] The auxiliary interception zone has interception fibers that form a porous structure. If the SEM average diameter of the interception fibers is too small, the holes in the auxiliary interception zone cannot be well supported. During the filtration process, the change in the flow rate of the fluid is likely to cause the destruction of the interception fibers, so that one or more holes are connected into a larger hole, thereby reducing the number of overlapping holes in the auxiliary interception zone, and failing to improve the overall interception efficiency of the membrane. If the SEM average diameter of the interception fibers is too large, the number of corresponding holes in the auxiliary interception zone will be reduced, and the number of overlapping holes in the auxiliary interception zone will also be reduced. However, because the ultrafiltration membrane of the present invention is a gradient pore size membrane and is formed from the first surface The average pore size of the main body in the thickness direction to the second surface first increases, then decreases, and then increases again, which brings about a relatively small change in the flow rate of the fluid passing through the ultrafiltration membrane. Therefore, the SEM average diameter of the auxiliary retention fiber can be smaller. We have found through continuous research that when the SEM average diameter of the retention fiber is 30nm-90nm, it can excellently support the holes in the auxiliary retention area, so that it can still protect the integrity of the holes in the auxiliary retention area under the impact of the change in the flow rate of the filtered fluid, thereby ensuring the integrity of the auxiliary retention area, achieving support for the second surface, and making the second surface have better compressive strength, thereby making the membrane as a whole have excellent mechanical strength. Further, under the synergistic effect of the overall porosity of the ultrafiltration membrane being 35%-70%, the obtained ultrafiltration membrane has excellent overall membrane flux, and the flux remains stable, excellent interception efficiency and overall membrane mechanical strength.
[0030] The SEM average diameter of the retained fibers can be measured by using a scanning electron microscope to characterize the morphology of the cross-section of the membrane-assisted retention area, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually measuring and performing corresponding calculations. For example, first use an electron microscope to characterize the cross-section of the membrane-assisted retention area to obtain the corresponding SEM image. The specific area size depends on the actual situation. Then use the corresponding computer software or manually measure the diameter of the retained fibers in the area (preferably more than 10 times, the specific number depends on the situation), and then calculate to obtain the average diameter of the retained fibers. Of course, technical personnel in this field can also obtain the above parameters by other measurement methods. The above measurement methods are for reference only.
[0031] As a further improvement of the present invention, the ultrafiltration membrane includes a separation zone, the separation zone includes a first surface, the thickness of the separation zone is 0.5μm-5μm; the ratio of the thickness of the separation zone to the thickness of the auxiliary retention zone is 0.1-0.3; and / or the ratio of the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole is 1.8-8.
[0032] As an internal pressure ultrafiltration membrane for clarifying ultrafiltration applications, its target molecules enter the membrane body through the first surface of the membrane and are collected through the second surface. By fully intercepting the impurity molecules, the target molecules in the filtrate have a higher purity, thereby improving the efficiency of clarifying ultrafiltration. Therefore, it is further preferred to set a separation zone including the first surface in the ultrafiltration membrane. When the filtered fluid passes through the separation zone, the impurity molecules not intercepted by the first surface are further captured in the separation zone. But at the same time, we also hope that the thickness of the separation zone is thinner, because the pore size in the separation zone is very small and the number of membrane pores is small. Once the thickness of the separation zone is slightly thicker, the overall flux of the membrane will become smaller, and a certain amount of target substances such as proteins may be adsorbed, resulting in a low final protein yield. Therefore, by adjusting the thickness of the separation zone to 0.5μm-5μm, it can not only further improve the overall interception efficiency of the membrane, but also have less impact on the flux, and still have a good overall membrane flux.
[0033] Furthermore, when the ratio of the thickness of the separation zone to the thickness of the auxiliary retention zone is 0.1-0.3, that is, the thickness of the separation zone is relatively thin, while the thickness of the auxiliary retention zone is relatively thick. Under the synergistic effect of the relatively thin thickness of the separation zone and the relatively thick thickness of the auxiliary retention zone, the membrane as a whole has both excellent retention efficiency and flux; and under the synergistic effect of the ratio of the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole being 1.8-8, preferably 1.8-7, more preferably 1.9-6, more preferably 1.9-5, and most preferably 1.9-4, the membrane as a whole has very excellent retention efficiency. At the same time, within the range of the ratio of the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole, the fluid passes through the membrane pores to make the flow rate of the fluid more stable, and a softer turbulence can be created on the first surface, which further reduces the damage to the protein target substance, but the relatively soft turbulence can still allow the fluid to carry away impurities retained by the first surface, thereby improving the retention efficiency.
[0034] The separation zone is located on one side of the first surface. The position of the separation zone is determined in the present invention by using a scanning electron microscope to characterize the morphology of the membrane cross section close to the first surface. For example, a scanning electron microscope image of the membrane cross section with a magnification of 20,000 or 50,000 is obtained. From the first surface to the second surface, the pore sizes of different planes are measured in sequence. The method is to select multiple holes on the same plane to measure their SEM pore sizes and calculate the average value until the average SEM pore size of the membrane pores on a certain plane is 1.2 times the SEM average pore size of the first hole. The plane is called interface P3, and the distance between interface P3 and the first surface is the thickness of the separation zone. The thickness of the separation zone is measured by measuring the distance from the first surface to the interface P3 on the cross-sectional SEM image of the membrane through computer software (such as Matlab, NIS-Elements, etc.) or manually. The average value calculated is the thickness of the separation zone.
[0035] As a further improvement of the present invention, the second surface comprises a plurality of second holes, and the ratio of the SEM average pore size of the second holes to the SEM average pore size of the first holes is 4-15; the hole area ratio of the second surface is 8%-35%, and the hole area ratio of the second surface is greater than the hole area ratio of the first surface.
[0036] The pore size of the second hole on the second surface of the ultrafiltration membrane has a great influence on the flux of the entire membrane, that is, if the pore size of the second hole is too small, the flux of the entire membrane will be slightly lower, and if the pore size of the second hole is too large, the compressive strength of the second surface will be low, causing the collapse or deformation of the second hole, affecting the mechanical strength of the entire membrane. Therefore, by adjusting the ratio of the SEM average pore size of the second hole to the SEM average pore size of the first hole to be 4-15, that is, the SEM average pore size of the second hole is larger than the SEM average pore size of the first hole, but not too large, the fluid can pass through the second hole faster, and the entire membrane has a better overall membrane flux. At the same time, the second surface of the membrane has excellent compressive strength, so that the entire membrane has good mechanical strength. At the same time, under the synergistic effect of the pore area rate of the second hole being 8%-35% and the pore area rate of the second hole being greater than the pore area rate of the first hole, the prepared membrane has a better overall membrane flux and overall membrane mechanical strength.
[0037] The measurement method of the SEM average pore size of the second hole refers to the measurement method of the SEM average of the first hole. The hole area ratio of the second surface is the ratio of the sum of the areas of all holes on the second surface to the area of the second surface. The measurement and calculation method thereof refers to the measurement and calculation method of the hole area ratio of the first surface.
[0038] As a further improvement of the present invention, the first hole is an elliptical structure, the long diameter direction of the first hole is parallel to the length direction of the ultrafiltration membrane, and the ratio C of the SEM average long diameter of the first hole to the SEM average pore diameter is 4-20;
[0039] The second hole is an elliptical structure, the long diameter direction of the second hole is parallel to the length direction of the ultrafiltration membrane, the ratio D of the SEM average long diameter of the second hole to the SEM average pore diameter is not greater than 5; and the ratio of C to D is 1.5-7.
[0040] The target substance of the ultrafiltration membrane used for clarifying filtration enters the membrane from the first surface and is then collected from the second surface. The filtered impurities are basically intercepted on the first surface, so the SEM average pore size of the first hole is very small. The present invention adjusts the ratio C of the SEM average length diameter of the first hole of the elliptical structure on the first surface to the SEM average pore size to be 4-20, that is, the SEM average length diameter of the first hole of the elliptical structure on the first surface is not too large (relatively large) compared with the SEM average pore size, because the first surface is the first to contact the filtered liquid during internal pressure filtration, and the corresponding external pressure is also increased. When the ratio C is 20 or more, the first surface is the first to contact the filtered liquid during internal pressure filtration, and the corresponding external pressure is also increased. When the ratio C is below 4, it can protect the first holes on the first surface from being damaged, so that the first surface has good compressive strength; at the same time, the SEM average major diameter of the first holes in the elliptical structure on the first surface will not be too small compared with the SEM average pore size, because the SEM average pore size of the first holes on the first surface is relatively small. When the ratio C is above 4, it has a larger first surface pore area ratio compared with the holes with a ratio C below 4, so that the membrane as a whole has a better flux. Therefore, by controlling the ratio C in the range of 4-20, the prepared ultrafiltration membrane can achieve both better overall membrane flux and mechanical strength.
[0041] Due to the needs of increasing the filtration flux and reducing the filtration pressure of the hollow fiber membrane used for clarifying ultrafiltration, the SEM average pore size of the second holes on the second surface used for clarifying ultrafiltration is usually relatively large. If the SEM average long diameter of the second holes is too large, the second holes are larger as a whole. Relatively speaking, the second holes are prone to collapse or deformation, which will reduce the compressive strength of the second surface, causing the overall stable flux and mechanical strength of the membrane to be slightly reduced. Therefore, by further regulating the ratio D of the SEM average long diameter of the elliptical second holes on the second surface to the SEM average pore size to be no more than 5 (that is, the ratio is very small), that is, the SEM average long diameter of the second holes is slightly larger than the SEM average pore size, and is relatively close to the SEM average pore size of the second holes, the ultrafiltration membrane prepared thereby has excellent overall stable flux and mechanical strength of the membrane.
[0042] Furthermore, under the synergistic effect of the ratio C of the SEM average long diameter to the SEM average pore size of the first hole and the ratio D of the SEM average long diameter to the SEM average pore size of the second hole being 1.5-7, that is, the ratio C is slightly larger than the ratio D, that is, the first hole is a narrower and longer hole than the second hole. In this way, under the effect of the special structure of the first holes on the first surface and the second holes on the second surface, the ultrafiltration membrane has better overall membrane flux, overall stable membrane flux and overall membrane mechanical strength.
[0043] The measuring method of the SEM average long diameter of the first hole and the SEM average long diameter of the second hole is similar to the SEM average pore size of the first hole and the SEM average pore size of the second hole. The pore size measured parallel to the length direction of the ultrafiltration membrane is the long diameter value of the hole.
[0044] As a further improvement of the present invention, the area between the second surface and the auxiliary retention zone is a steady flow zone, and the thickness of the steady flow zone is 1μm-15μm; the ratio of the SEM average pore size of the steady flow zone to the SEM average pore size of the auxiliary retention zone is 1.2-4; and / or, the steady flow zone also includes flow stabilizing fibers forming a porous structure of the steady flow zone, and the ratio of the SEM average diameter of the flow stabilizing fibers to the SEM average diameter of the retention fibers is 1.1-2.
[0045] In the main structure of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared by us, the area between the interface P1 and the second surface is called the steady flow zone. By controlling the ratio of the SEM average pore size of the steady flow zone to the SEM average pore size of the auxiliary retention zone to be 1.2-4, that is, the SEM average pore size of the steady flow zone is slightly larger than the SEM average pore size of the auxiliary retention zone, the flow velocity of the fluid changes less when the fluid flows from the auxiliary retention zone to the steady flow zone. Since the impact force of the flow velocity change on the second surface is smaller, it is beneficial to protect the strength of the second surface, so that the membrane as a whole has excellent mechanical strength. Further, the flow velocity changes less, and the shear force on the filtered liquid in the ultrafiltration membrane body is also smaller, which reduces the damage to the protein target substance and further improves the yield of the target substance. Under the synergistic effect of the ratio of the SEM average pore size of the steady flow zone to the SEM average pore size of the auxiliary retention zone being 1.2-4, the thickness of the steady flow zone (the average distance from the interface P1 to the second surface) can be slightly thicker, that is, the SEM average pore size of the steady flow zone is slightly larger than the SEM average pore size of the auxiliary retention zone. When the thickness of the steady flow zone is slightly thicker, it can still provide good support for the second surface and protect the second holes on the second surface from deformation or collapse, so that the membrane as a whole has a stable flux and good mechanical strength. At the same time, when the thickness of the steady flow zone is slightly thicker (not too thin), the membrane filaments may be squeezed under the action of external forces, for example when assembled into a hollow fiber membrane assembly. The existence of the steady flow zone can protect the auxiliary retention zone from squeezing, etc., and protect the integrity of the auxiliary retention zone, so that the membrane as a whole has a better retention efficiency, and the retention efficiency of impurities is relatively stable.
[0046] Similarly, the stabilizing flow zone has stabilizing fibers that form a porous structure. By regulating the ratio of the SEM average diameter of the stabilizing flow fibers to the SEM average diameter of the retained fibers within a reasonable range, that is, the SEM average diameter of the stabilizing flow fibers is slightly larger than the SEM average diameter of the retained fibers, it can better support the holes in the stabilizing flow zone, and then better support the second holes on the second surface, so that the membrane as a whole has good mechanical strength. At the same time, the flow velocity changes little when the fluid flows from the retained retention zone to the stabilizing flow zone, that is, the flow velocity is relatively stable, and the shear force generated is extremely small or even no shear force is generated, which will not cause damage to the target protein, further improving the yield of protein target substances.
[0047] The thickness of the steady flow zone is the distance B from the interface P1 of the auxiliary retention zone to the second surface, and the SEM average pore size of the pores in the steady flow zone and the SEM average diameter of the steady flow fibers are obtained in the same way as the thickness of the auxiliary retention zone, the SEM average pore size of the pores in the auxiliary retention zone and the SEM average diameter of the retained fibers.
[0048] As a further improvement of the present invention, the thickness of the flow stabilizing zone is 0.05-0.12 of the overall membrane thickness; the SEM average pore size of the flow stabilizing zone is 40nm-1000nm; and / or the SEM average diameter of the flow stabilizing fiber is 40nm-100nm.
[0049] Preferably, the SEM average pore size of the steady flow zone is 40nm-1000nm, which is slightly larger than the SEM average pore size of the auxiliary interception zone, so that the membrane as a whole has better overall membrane flux and mechanical strength, and protein target substance yield. At the same time, the thickness of the steady flow zone is 0.05-0.12 of the overall thickness of the membrane, that is, the thickness of the steady flow zone is relatively small relative to the overall thickness of the membrane, which has the function of protecting the auxiliary interception zone, and at the same time can maintain the supporting effect of the auxiliary interception zone on the outer surface, so that the membrane has a more stable flux and better mechanical strength. At the same time, by adjusting the SEM average diameter of the steady flow fiber to 40nm-100nm, the membrane as a whole further has better mechanical strength and protein target substance yield.
[0050] As a further improvement of the present invention, the tensile strength of the ultrafiltration membrane is not less than 120cN; the thickness of the ultrafiltration membrane is 90μm-200μm; the internal explosion pressure of the ultrafiltration membrane is greater than 0.2MPa; the initial yield of the ultrafiltration membrane for the target substance is more than 90%; and / or the yield of the target substance of the ultrafiltration membrane after 10 complete uses is more than 80% of the initial yield.
[0051] After mechanical strength test, the tensile strength of the ultrafiltration membrane prepared by the present invention is not less than 120cN, which has excellent mechanical properties and high industrial practical value. It can also be shown that the compressive strength of the first surface and the second surface of the ultrafiltration membrane are both high, and it can withstand the operating pressure and changes in the operating pressure during the ultrafiltration process for a long time, and can work normally for a long time under relatively high pressure.
[0052] The samples were stretched at a constant speed using a stretching machine at room temperature (stretching speed was 50 mm / min, and the distance between the upper and lower clamps was 30 mm) until they broke, thereby measuring the tensile strength. This was repeated three times and the average value was taken. The average value obtained was the final tensile strength.
[0053] The implosion pressure of an ultrafiltration membrane refers to the maximum pressure that the ultrafiltration membrane can withstand without breaking under the action of internal pressure. The magnitude of the implosion pressure reflects the maximum pressure that the ultrafiltration membrane can withstand. The greater the implosion pressure, the higher the compressive strength of the membrane. The implosion pressure of the asymmetric sulfone polymer hollow ultrafiltration membrane of the present invention is greater than 0.2MPa, and its implosion pressure can meet the needs of practical applications, indicating that the ultrafiltration membrane has good compressive strength.
[0054] The test method for implosion pressure is: (1) according to Fig. 9Connect the hollow fiber membrane assembly (the shell containing the hollow fiber membrane is transparent, so that the membrane fibers inside the hollow fiber membrane assembly can be observed with the naked eye), pressure gauge 1, pressure gauge 2, peristaltic pump, feed liquid container (containing purified water), valve 1, valve 2 and receiving bottle to form a circulation system; (2) open all valves to allow purified water to circulate in the system for 10 minutes to moisten the membrane fibers, then close valve 2, and allow purified water to enter the hollow fiber membrane assembly through the liquid inlet end (connected to the first surface of the hollow fiber membrane), and at the same time gradually increase the pressure of pressure gauge 1 from 0.1 MPa, and observe the changes in the membrane fibers. When the membrane fibers are observed to rupture, record the value P1 of pressure gauge 1 and the value P2 of pressure gauge 2. (P1+P2) / 2 is the implosion pressure of the ultrafiltration membrane.
[0055] The initial yield of the target substance of the asymmetric sulfone polymer hollow ultrafiltration membrane is more than 90%, which shows that the target substance in the fluid is less damaged and adsorbed during the filtration process, and the economic efficiency is relatively high. At the same time, after 10 complete uses of the ultrafiltration membrane (1 complete use means that the material of the clarified ultrafiltration is separated and purified once in the hollow fiber membrane assembly, and then the hollow fiber membrane assembly is cleaned and regenerated with a cleaning liquid, and the yield of the target substance tested is the yield of the target substance for 1 complete use, and accordingly, 10 times of separation, purification and cleaning is 10 complete uses), the yield of the target substance is more than 80% of the initial yield of the target substance. It can be seen that the ultrafiltration membrane prepared by the present invention has good anti-pollution performance and regeneration effect, and has a long service life.
[0056] Test method for target substance yield:
[0057] Step 1: Follow Fig. 9 Connect the hollow fiber membrane assembly, pressure gauge 1, pressure gauge 2, peristaltic pump, liquid container (containing the substance to be clarified and filtered), valve 1, valve 2 and receiving bottle in sequence to form a circulation system;
[0058] Step 2: Turn on the peristaltic pump and run at 2000s -1 -6000s -1 Adjust the pump speed according to the shear rate to fill the pipeline with liquid and remove the air in the pipeline;
[0059] Step 3: by adjusting the valve at the reflux end so that the pressure gauge reading is between 5-30psi, the target substance solution passing through the membrane assembly is received by the receiving bottle until the yield of the target substance in the receiving bottle no longer increases, wherein the method for judging that the yield of the target substance no longer increases is that the product of the concentration C2 of the target substance in the permeate and the volume V2 of the permeate no longer increases, and the method for calculating the yield of the target substance is: (volume V2 of the permeate*concentration C2 of the target substance in the permeate) / (volume V1 of the initial sample load*concentration C1 of the target substance in the initial sample load), wherein the volume V1 of the initial sample load and the volume V2 of the permeate are obtained by a measuring cylinder or other commonly used means, and the concentration C1 and the concentration C2 of the target substance in the initial sample load can be measured by a Cedex biochemical analyzer, an ultraviolet spectrophotometer, semi-quantitative SDS gel electrophoresis, reverse phase / liquid chromatography analysis, etc. Specifically, it is selected according to the specific type of the target substance, for example, the concentration of 30kD of the insulin refolding solution can be measured by a Cedex biochemical analyzer.
[0060] As a further improvement of the present invention, the ultrafiltration membrane is sponge-shaped. Compared with the pore-shaped structure, the sponge-shaped hollow fiber ultrafiltration membrane has better compressive strength and overall mechanical strength and tensile strength of the membrane (the hollow fiber membrane with a pore-shaped structure has the disadvantages of easy breakage of internal fibers, which may cause the collapse of the entire membrane, poor pore size controllability, which may affect the filtration progress, and high requirements on the diameter of the fibers supporting the pore structure).
[0061] The second aspect of the present invention provides a method for preparing the above-mentioned asymmetric sulfone polymer hollow ultrafiltration membrane, comprising the following steps:
[0062] Step 1: Prepare casting liquid and core liquid:
[0063] The casting solution comprises 15-30 parts by weight of a sulfone polymer, 40-60 parts by weight of a first organic solvent, 15-25 parts by weight of a hydrophilic additive, and 20-40 parts by weight of a non-solvent additive;
[0064] The core liquid comprises a second organic solvent and water, wherein the mass content of water in the core liquid is 60%-100%;
[0065] Step 2: Spinning: Extruding the casting solution and the core solution obtained in step 1 from a spinneret together to form a molded product having a first surface and a second surface;
[0066] Step 3: Pre-phase separation: The molded product obtained in step 2 is pre-phased in an air section to form a green film I, wherein the relative humidity of the air section is 60%-100%, and the pre-phase separation time is 1.5s-3s;
[0067] Step 4: Complete phase separation: immersing the raw film I obtained in step 3 into a coagulation bath for complete phase separation to obtain raw film II, wherein the coagulation bath is composed of a third organic solvent, water and a surfactant, and the mass content of the surfactant is 0.5%-5% of the coagulation bath solvent;
[0068] The mass content of water in the coagulation bath is not less than 30%; the complete phase separation time is 50s-150s;
[0069] Step 5: Cleaning and drying: The raw membrane II obtained in step 4 is cleaned with pure water and then dried to obtain an asymmetric sulfone polymer hollow ultrafiltration membrane;
[0070] The sulfone polymer is at least one of bisphenol A polysulfone, polyethersulfone, polyphenylsulfone and sulfonated polyethersulfone;
[0071] The first organic solvent, the second organic solvent and the third organic solvent are at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide;
[0072] The hydrophilic additive is at least one of polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polyethylene imine;
[0073] The non-solvent additive is at least one of water, isopropanol, glycerol and butanediol;
[0074] The surfactant is at least one of Tween 80, Tween 20, sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and poloxamer.
[0075] As a further improvement of the present invention, the solid content of the casting liquid is not less than 20%; the mass ratio between the non-solvent additive and the first organic solvent in the step one is 0.4-0.8; and / or the mass ratio of the hydrophilic additive to the casting liquid in the step one is 0.1-0.2, and the ratio of the sum of the mass of the hydrophilic additive and the non-solvent to the mass of the casting liquid is not greater than 0.5.
[0076] As a further improvement of the present invention, the temperature of the coagulation bath in step four is 20-60°C, and the pre-phase separation temperature in step three is at least 20°C higher than the temperature of the coagulation bath; and / or, the ratio of the complete phase separation time in step four to the pre-phase separation time in step three is 35-80; and / or, the running speed of the membrane in step three and step four is 1m / min-10m / min.
[0077] As a further improvement of the present invention, the air bath temperature in step three is 50-95°C; and / or the casting liquid temperature in step two is 10-40°C, and the casting liquid temperature is at least 5°C lower than the coagulation bath temperature.
[0078] When preparing the asymmetric sulfone polymer hollow ultrafiltration membrane of the present invention, a casting solution is first prepared, wherein the casting solution includes 15-30 parts by weight of a membrane-forming substance sulfone polymer, 40-60 parts by weight of a first organic solvent for dissolving the sulfone polymer, 15-25 parts by weight of a hydrophilic additive, and 20-40 parts by weight of a non-solvent additive;
[0079] The addition of hydrophilic additives can not only improve the hydrophilicity of the ultrafiltration membrane, but also ultimately make the filter membrane have good hydrophilicity and ensure the protein yield. At the same time, the amount of hydrophilic additives is controlled within a certain range to ensure that the hydrophilic additives in the finished ultrafiltration membrane will not be dissolved. At the same time, under the synergistic effect of non-solvent additives, the viscosity of the casting liquid system can be effectively controlled, which can effectively affect the overall retention efficiency and flux of the membrane. The viscosity of the casting liquid has a great influence on the structure and performance of the filter membrane finally formed, such as affecting the pore size, thickness, flow rate, etc. of the ultrafiltration membrane. By regulating the mass ratio of sulfone polymer, first organic solvent, hydrophilic additive and non-solvent, the prepared casting liquid has a suitable viscosity, so that the final asymmetric sulfone polymer hollow ultrafiltration membrane has a suitable thickness, ideal membrane pore structure and pore size, and is effectively used in clarification ultrafiltration.
[0080] The inner core used in the extrusion of the hollow fiber ultrafiltration membrane of the present invention is a liquid composed of a second organic solvent and water. By reasonably controlling the mass content of water in the core liquid, not only can the pressure in the cavity of the hollow fiber ultrafiltration membrane be balanced with the external pressure, thereby stabilizing the cavity of the hollow fiber ultrafiltration membrane so that the overall wall thickness of the membrane is basically the same, but also, under the joint action of other conditions such as a coagulation bath, by controlling the speed change of the membrane phase separation process, an asymmetric sulfone polymer hollow ultrafiltration membrane with an ideal pore size distribution can be manufactured.
[0081] Preferably, by further regulating the solid content of the casting liquid to be not less than 20%, that is, the mass content of the sulfone polymer in the casting liquid is relatively high, the mass ratio of the non-solvent additive to the first organic solvent is 0.4-0.8, that is, the non-solvent is relatively less than the first solvent, the mass ratio of the hydrophilic additive to the casting liquid is 0.1-0.2, that is, the hydrophilic additive is controlled within a reasonable range, the ratio of the sum of the mass of the hydrophilic additive and the non-solvent to the mass of the casting liquid is not greater than 0.5, that is, the ratio of the sum of the mass of the hydrophilic additive and the non-solvent to the mass of the casting liquid is controlled within a reasonable range, and by controlling each component in the casting liquid within a preferred range, the casting liquid has a more suitable viscosity, and under the joint action of other conditions such as pre-phase separation and coagulation bath, the casting liquid of the specific composition tends to phase separate into a membrane with a gradual pore size and a structure in which the pore size first increases, then decreases, and then increases in the direction from the first surface to the second surface during the phase separation process; at the same time, the membrane pollution and membrane pore blockage caused by the dissolution of hydrophilic substances when the ultrafiltration membrane is used for clarifying ultrafiltration are avoided, the membrane pores are more uniform, and the membrane as a whole has a higher porosity.
[0082] The second step is to extrude the prepared casting liquid and core liquid from the spinneret together. The casting liquid forms a molded product having a first surface and a second surface in the nozzle, namely, a hollow fiber membrane. The extruded hollow fiber membrane has a first surface facing the inner cavity and a second surface opposite to the cavity.
[0083] In the pre-phase separation of step three, the molded product obtained in step two is passed through an air section. During the pre-phase separation, since the first surface is in direct contact with the core liquid, under the synergistic effect of the water mass content of 60%-100% in the core liquid and the overall specific composition of the casting liquid, the phase separation speed of the first surface is faster and small holes are easily formed. Under the synergistic effect of the pre-phase separation time of 1.5s-3s (short time), the pore area ratio of the first surface is relatively low, which is conducive to obtaining the membrane pore structure of the first surface required by the present invention.
[0084] At the same time, in the process of pre-phase separation, the molded product is placed in an air segment with a humidity of 60%-100% for pre-phase separation. The pre-phase separation time is 1.5-3s. Under the combined effect of factors such as an air segment with a certain humidity (the air contains a certain amount of water vapor), pre-phase separation time and casting liquid, holes with suitable pore diameters and suitable pore area ratios appear on the second surface (that is, the outer surface obtains an open macroporous structure). The pore diameter of the second hole is larger than that of the first hole, ensuring that the hollow fiber membrane has a good water flux.
[0085] Preferably, the phase separation speed of the membrane filaments is also related to the temperature and its temperature difference. The larger the temperature difference, the faster the membrane is during the pre-phase separation process. The temperature of the casting liquid in step two is 10-40°C and the air bath temperature of the pre-phase separation in step three is 50-95°C, that is, the difference between the pre-phase separation temperature and the casting liquid temperature is between 10°C-85°C, which has a reasonable temperature difference range. Under the interaction of factors such as the viscosity of the casting liquid, the second surface of the obtained ultrafiltration membrane has a more excellent pore size and pore area ratio (the membrane pores are more uniform and the number of membrane pores is greater).
[0086] Next, the pre-phase-separated raw membrane I is immersed in a coagulation bath for complete phase separation treatment, wherein the coagulation bath is composed of a third organic solvent, water and a surfactant, and the mass content of water in the coagulation bath is not less than 30%, that is, there is more water in the coagulation bath, and due to the effect of pre-phase separation, second holes of a certain pore size and a certain number have appeared on the second surface, and water can penetrate into the membrane filaments relatively easily. At the same time, with the auxiliary effect of the surfactant in the coagulation bath (at least one of Tween 80, Tween 20, sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and poloxamer), the penetration of water into the membrane filaments can be further accelerated. When the mass content of the surface active agent in the coagulation bath is 0.5%-5%, the water content of the surface active agent in the coagulation bath is 0.5%. Within the dosage range of the agent, it can be ensured that the speed of water infiltration into the membrane filaments is within a reasonable range, that is, neither too fast nor too slow, so that the amount of water entering each part of the membrane filaments is relatively uniform, and at the same time, under the synergistic effect of the specific composition of the casting liquid, an ultrafiltration membrane with a gradient pore size is formed in the thickness direction from the first surface to the second surface, in which the average pore size of the main body first increases, then decreases, and then increases again, that is, the pore size of the formed ultrafiltration membrane changes slowly, that is, there are no cracks in the scanning electron microscope image at a magnification of 60× disclosed in the CN114452844A patent, and accordingly, an auxiliary retention zone is formed in the transition zone of the pore size "decrease and then increase", and the membrane is fully phase-separated after 50s-150s of phase separation to obtain raw membrane II.
[0087] Temperature and temperature changes will also have a certain impact on the phase separation speed of the membrane. Preferably, by controlling the temperature of the coagulation bath to 20-60°C and the pre-phase separation temperature to be at least 20°C higher than the temperature of the coagulation bath, the phase separation speed of the membrane is more stable under the synergistic effect of a specific temperature and a specific temperature difference, and the pore size of the formed ultrafiltration membrane changes more slowly. Furthermore, in step 4, the ratio of the complete phase separation time to the pre-phase separation time in step 3 is within a reasonable range, and the speed of the membrane operation in steps 3 and 4 is within a reasonable range. Under the synergistic effect, the prepared ultrafiltration membrane is more fully phase-separated in the coagulation bath.
[0088] The raw membrane II obtained after phase separation is washed in water and then dried to obtain an asymmetric sulfone polymer hollow ultrafiltration membrane.
[0089] The third aspect of the present invention provides an application of an asymmetric sulfone polymer hollow ultrafiltration membrane, which is used for: (a) removing endotoxins from raw materials of chemical drugs; (b) removing endotoxins from raw materials of traditional Chinese medicine preparations; (c) removing macromolecular impurities in insulin intermediates; (d) collecting recombinant proteins from cell fragments / large intestine homogenate; (e) extracting and purifying proteins and enzymes from fermentation broth; (f) extracting virus particles from cell culture medium; (g) extracting and purifying nucleic acids from cell lysate; and (h) extracting monoclonal antibodies from hybridoma cell culture medium.
[0090] Compared with the prior art, the present invention has the following beneficial technical effects:
[0091] 1. The present invention scientifically regulates the structure of the main body of the asymmetric sulfone polymer hollow ultrafiltration membrane to contain an auxiliary retention zone, a non-directional tortuous passage, the average pore size of the main body in the thickness direction from the first surface to the second surface first increases, then decreases, and then increases again, the ultrafiltration membrane is a gradient pore size membrane, and the ratio of the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole, the nearest average distance from the auxiliary retention zone to the first surface, and the overall porosity of the membrane are within a reasonable range. When the pore size of the first hole on the first surface of the prepared ultrafiltration membrane is relatively slightly larger, excellent retention efficiency can be obtained, while still having good overall membrane flux and stable membrane flux. Under the special structure of the membrane, the turbulence brought to the first surface by the relatively small flow rate change of the fluid passing through the interior of the fluid can reduce the damage of the protein target substance, and has a good yield of protein substances, with unexpected technical effects.
[0092] 2. In the process of preparing the asymmetric sulfone polymer hollow ultrafiltration membrane of the present invention, by scientifically regulating the specific composition of the casting liquid, the specific humidity air segment in the pre-phase separation, the reasonable amount of surfactant and the reasonable amount of water in the coagulation bath, the prepared membrane has a non-directional tortuous path, the average pore size of the main body in the thickness direction from the first surface to the second surface first increases, then decreases, and then increases again, the ultrafiltration membrane is a gradient pore size membrane, and the auxiliary retention zone structure, and at the same time, the ratio of the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole, the nearest average distance from the auxiliary retention zone to the first surface, and the overall porosity of the membrane are within a reasonable range.
[0093] 3. The asymmetric sulfone polymer hollow ultrafiltration membrane of the present invention is integrally formed by a casting liquid, and has the advantages of simple preparation method, better cost, green environmental protection, and suitability for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0094] Figure 1 This is a schematic scanning electron microscope (SEM) image of the first surface of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1, wherein the magnification is 20000×.
[0095] Figure 2 This is a further magnified scanning electron microscope (SEM) schematic diagram of the first surface of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1, wherein the magnification is 50000×.
[0096] Figure 3 This is a schematic scanning electron microscope (SEM) image of the second surface of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1, wherein the magnification is 5000×.
[0097] Figure 4 This is a schematic diagram of a scanning electron microscope (SEM) of a further method for the second surface of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1, wherein the magnification is 10000×.
[0098] Figure 5 This is a schematic scanning electron microscope (SEM) image of the entire asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1, wherein the magnification is 60×.
[0099] Figure 6 This is a further magnified scanning electron microscope (SEM) schematic diagram of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1, wherein the magnification is 500×.
[0100] Figure 7 This is a schematic scanning electron microscope (SEM) image of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1 near the second surface, wherein the magnification is 10000×.
[0101] Figure 8 This is a schematic scanning electron microscope (SEM) diagram of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Example 1 near the first surface, wherein the magnification is 20000×.
[0102] Fig. 9 Schematic diagram of the test equipment for interception efficiency, water flux test, implosion pressure and target substance yield. DETAILED DESCRIPTION
[0103] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0104] Example 1
[0105] Step 1: Preparation of casting liquid and core liquid
[0106] The casting solution comprises the following materials in parts by weight: 30 parts by weight of polyethersulfone, 40 parts by weight of dimethylacetamide, 22 parts by weight of polyvinylpyrrolidone, and 22 parts by weight of water. The temperature is 10° C. and the solid content is 26%.
[0107] The core liquid includes dimethylacetamide and water, wherein the mass content of water in the core liquid is 95%;
[0108] Step 2: Extruding the casting liquid and the core liquid obtained in step 1 from a spinneret together to form a molded product having a first surface and a second surface;
[0109] Step 3: Pre-phase separation of the molded product. The molded product obtained in step 2 is pre-phased in an air section with a relative humidity of 98% and a temperature of 90° C. for 1.6 seconds to form a raw film I. The running speed of the film is 8 m / min.
[0110] Step 4: immersing the obtained raw membrane I in a coagulation bath at 50° C. for 60 seconds to perform complete phase separation treatment to obtain raw membrane II, wherein the coagulation bath is composed of 95% by weight water and 5% by weight Tween, and the membrane is operated at a speed of 8 m / min;
[0111] Step 5: Wash the raw membrane II obtained in step 4 with pure water and then dry it to obtain a 5kD asymmetric polyethersulfone hollow ultrafiltration membrane.
[0112] Example 2
[0113] Step 1: Preparation of casting liquid and core liquid
[0114] The casting solution comprises the following materials in parts by weight: 28 parts by weight of polyphenylsulfone, 40 parts by weight of N-methylpyrrolidone, 15 parts by weight of polyethylene glycol, and 30 parts by weight of isopropanol. The temperature is 30° C. and the solid content is 25%.
[0115] The core liquid includes N-methylpyrrolidone and water, wherein the mass content of water in the core liquid is 90%;
[0116] Step 2: Extruding the casting liquid and the core liquid obtained in step 1 from a spinneret together to form a molded product having a first surface and a second surface;
[0117] Step 3: Pre-phase separation of the molded product. The molded product obtained in step 2 is pre-phased in an air section with a relative humidity of 86% and a temperature of 85° C. for 1.8 seconds to form a raw film I. The running speed of the film is 7 m / min.
[0118] Step 4: immersing the obtained raw membrane I in a coagulation bath at 60° C. for 80 seconds to perform complete phase separation treatment to obtain raw membrane II, wherein the coagulation bath is composed of 17% by mass of N-methylpyrrolidone, 80% by mass of water, and 3% by mass of dodecyl sulfuric acid, and the membrane runs at a speed of 7 m / min;
[0119] Step 5: Wash the raw membrane II obtained in step 4 with pure water and then dry it to obtain a 30 kD asymmetric polyphenylsulfone hollow ultrafiltration membrane.
[0120] Example 3
[0121] Step 1: Preparation of casting liquid and core liquid
[0122] The casting solution comprises the following materials in parts by weight: 26 parts by weight of polyethersulfone, 45 parts by weight of dimethylacetamide, 20 parts by weight of polyethyleneimine and 25 parts by weight of water, with a temperature of 25° C. and a solid content of 22%.
[0123] The core liquid includes dimethylacetamide and water, wherein the mass content of water in the core liquid is 85%;
[0124] Step 2: Extruding the casting liquid and the core liquid obtained in step 1 from a spinneret together to form a molded product having a first surface and a second surface;
[0125] Step 3: Pre-phase separation of the molded product. The molded product obtained in step 2 is pre-phased in an air section with a relative humidity of 82% and a temperature of 70° C. for 2 seconds to form a raw film I. The running speed of the film is 5 m / min.
[0126] Step 4: immersing the obtained raw film I in a coagulation bath at 45° C. for 120 seconds for complete phase separation to obtain raw film II, wherein the coagulation bath is composed of 36% by mass of dimethylacetamide, 60% by mass of water, and 4% by mass of hexadecyltrimethylammonium chloride, and the running speed of the film is 5 m / min;
[0127] Step 5: Wash the raw membrane II obtained in step 4 with pure water and then dry it to obtain a 50kD asymmetric polyethersulfone hollow ultrafiltration membrane.
[0128] Example 4
[0129] Step 1: Preparation of casting liquid and core liquid
[0130] The casting solution comprises the following materials in parts by weight: 24 parts by weight of polyethersulfone, 48 parts by weight of dimethylformamide, 18 parts by weight of polyethylene glycol, and 28 parts by weight of water. The temperature is 35° C. and the solid content is 20%.
[0131] The core liquid includes dimethylformamide and water, wherein the mass content of water in the core liquid is 80%;
[0132] Step 2: Extruding the casting liquid and the core liquid obtained in step 1 from a spinneret together to form a molded product having a first surface and a second surface;
[0133] Step 3: Pre-phase separation of the molded product. The molded product obtained in step 2 is pre-phased in an air section with a relative humidity of 75% and a temperature of 75° C. for 2.3 seconds to form a raw film I. The running speed of the film is 3 m / min.
[0134] Step 4: immersing the obtained raw membrane I in a coagulation bath at 55° C. for 100 seconds for complete phase separation to obtain raw membrane II, wherein the coagulation bath is composed of 48% by mass of dimethylformamide, 50% by mass of water, and 2% by mass of Tween 80, and the membrane runs at a speed of 3 m / min;
[0135] Step 5: Wash the raw membrane II obtained in step 4 with pure water and then dry it to obtain a 100 kD asymmetric polyethersulfone hollow ultrafiltration membrane.
[0136] Example 5
[0137] Step 1: Preparation of casting liquid and core liquid
[0138] The casting solution comprises the following materials in parts by weight: 22 parts by weight of sulfonated polyethersulfone, 42 parts by weight of dimethyl sulfoxide, 15 parts by weight of polyvinyl alcohol, and 32 parts by weight of glycerol. The temperature is 20° C. and the solid content is 20%.
[0139] The core liquid includes dimethyl sulfoxide and water, wherein the mass content of water in the core liquid is 70%;
[0140] Step 2: Extruding the casting liquid and the core liquid obtained in step 1 from a spinneret together to form a molded product having a first surface and a second surface;
[0141] Step 3: Pre-phase separation of the molded product. The molded product obtained in step 2 is pre-phased in an air section with a relative humidity of 66% and a temperature of 50° C. for 2.6 seconds to form a raw film I. The running speed of the film is 2 m / min.
[0142] Step 4: immersing the obtained raw membrane I in a coagulation bath at 30° C. for 140 seconds for complete phase separation to obtain raw membrane II, wherein the coagulation bath is composed of 64.5% by weight of dimethyl sulfoxide, 35% by weight of water, and 0.5% by weight of poloxamer, and the membrane runs at a speed of 2 m / min;
[0143] Step 5: Wash the raw membrane II obtained in step 4 with pure water and then dry it to obtain a 300 kD asymmetric sulfonated polyethersulfone hollow ultrafiltration membrane.
[0144] The structure, overall porosity, overall tensile strength, implosion pressure, and roughness of the first surface of the asymmetric sulfone polymer hollow ultrafiltration membrane prepared in Examples 1-5 were characterized, and the specific results are shown below:
[0145] Table 1 - Overall characteristics of ultrafiltration membrane
[0146] sample Example 1 Example 2 Example 3 Example 4 Example 5 Overall film thickness / μm 105 120 170 130 140 Overall membrane porosity / % 48.47 54.21 63.46 61.74 68.12 Tensile strength of the entire membrane / cN 194 186 208 172 184 Implosion pressure / MPa 0.6 0.5 0.6 0.4 0.4
[0147] Table 2 - Characteristics of the first and second surfaces
[0148]
[0149]
[0150] Table 3 - Characteristics of the auxiliary retention zone
[0151]
[0152] Table 4 - Characteristics of the separation zone
[0153] sample Example 1 Example 2 Example 3 Example 4 Example 5 Thickness of separation zone / μm 1.7 2.1 3.8 3.3 4.1 Thickness of separation zone / thickness of auxiliary retention zone 0.17 0.14 0.19 0.17 0.21
[0154] Table 5 - Characteristics of steady flow region
[0155]
[0156]
[0157] Characterization of interception efficiency
[0158] The interception efficiency test method is as follows:
[0159] Step 1: Follow Fig. 9 Connect the hollow fiber membrane module, pressure gauge 1, pressure gauge 2, peristaltic pump, liquid container (containing the substance to be tested for interception), valve 1, valve 2 and receiving bottle in sequence to form a circulation system;
[0160] Step 2: Turn on the peristaltic pump and run at 6000s -1 Adjust the pump speed according to the shear rate to fill the pipeline with liquid and remove the air in the pipeline;
[0161] Step 3: Adjust the reflux valve so that the pressure gauge reading is between 8-16 psi. When the trapped material is about to drip out, press the stopwatch to start timing. Take a sample after 10 minutes and test its absorbance on a UV spectrophotometer, record it as A 透过 The absorbance of the original solution of the retained substance is recorded as A 原液 , its interception efficiency = 1-A 透过 / A 原液, The detailed results are shown in Table 6 below:
[0162] Table 6 - Retention efficiency of ultrafiltration membrane
[0163]
[0164] Characterization of water flux
[0165] The test method for water flux is as follows:
[0166] Step 1: Follow Fig. 9Connect the hollow fiber membrane assembly, pressure gauge 1, pressure gauge 2, peristaltic pump, liquid container (filled with purified water), valve 1, valve 2 and receiving bottle in sequence to form a circulation system;
[0167] Step 2: Adjust the transmembrane pressure to 5psi. After the permeate flow rate stabilizes for 3 minutes, collect the permeate in a beaker and press the stopwatch at the same time. Stop collecting the liquid after 1 minute, weigh and record the data. Repeat 3 times to calculate the average value. Measure the water temperature at the same time and convert it to the value of LMH / psi at 25°C according to the viscosity coefficient. This is the water flux of the membrane fiber. The results are shown in Table 7.
[0168] Table 7 - Water flux of ultrafiltration membrane
[0169] sample Example 1 Example 2 Example 3 Example 4 Example 5 Initial water flux / LMH / psi 7.67 26.75 36.36 79.45 235.23
[0170] The results of the target substance yield are shown in Table 8:
[0171] Table 8 - Target substance yield of ultrafiltration membrane
[0172]
[0173] Example 6
[0174] A 100 kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the casting solution in step one contained 20 parts by mass of polyethersulfone and had a solid content of 17%, the water content in the coagulation bath in step four was 40%, and the temperature of the coagulation bath was 35 ° C. The SEM average pore size of the auxiliary retention zone of the finally obtained asymmetric polyethersulfone hollow ultrafiltration membrane was 800 nm. Compared with Example 4, the overall retention efficiency of the membrane in Example 6 was relatively low, and the retention efficiency of 500 kD of dextran was 95%.
[0175] Example 7
[0176] A 100kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the casting liquid in step one contained 25 parts by mass of polyethylene glycol, 30 parts by mass of glycerol, no water, and a solid content of 19%. The mass content of water in the core liquid in step one was 90%. The initial water contact angle of the first surface of the finally obtained asymmetric polyethersulfone hollow ultrafiltration membrane was 35°. Compared with Example 4, the first surface of the ultrafiltration membrane prepared in Example 7 was more hydrophilic. When it was used for clarifying filtration, polyethylene glycol was dissolved, so that the dissolved polyethylene glycol blocked the membrane pores, resulting in a slightly lower overall membrane flux, and its initial water flux was 75.83LMH / psi.
[0177] Example 8
[0178] A 100kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the casting liquid in step one contained 22 parts by mass of polyethersulfone and 38 parts by mass of water, and the solid content thereof was 17%, the mass content of water in the coagulation bath in step four was 30%, and the temperature of the coagulation bath was 15°C. The thickness of the auxiliary retention zone of the finally obtained asymmetric polyethersulfone hollow ultrafiltration membrane was 25 μm, and the average distance from the auxiliary retention zone to the second surface was 18 μm. Compared with Example 4, the flux of the ultrafiltration membrane prepared in Example 8 was slightly lower, which was 74.24 LMH / psi.
[0179] Example 9
[0180] A 100 kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by the preparation method of Example 4, except that the casting solution in step one contained 15 parts by mass of polyethersulfone and 40 parts by mass of water, and the solid content was 12%, the air section temperature in step three was 55 ° C, and the coagulation bath temperature in step four was 65 ° C. The SEM average diameter of the retention fiber in the auxiliary retention zone of the finally obtained asymmetric polyethersulfone hollow ultrafiltration membrane was 25 nm. Compared with Example 4, the ultrafiltration membrane prepared in Example 9 had a slightly lower retention efficiency of 93% for dextran 500 kD.
[0181] Example 10
[0182] A 100kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the casting liquid in step one contained 28 parts by mass of polyethersulfone and 20 parts by mass of isopropanol, did not contain water, and had a solid content of 25%. The mass content of water in the core liquid in step one was 90%, and the air section temperature in step three was 45°C. The separation zone thickness of the finally obtained asymmetric polyethersulfone hollow ultrafiltration membrane was 8 μm. Compared with Example 4, the initial water flux of the ultrafiltration membrane of Example 10 was relatively lower, which was 73.61 LMH / psi.
[0183] Embodiment 11
[0184] A 100kD asymmetric sulfonated polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the casting liquid in step one contained 24 parts by mass of sulfonated polyethersulfone and 28 parts by mass of butanediol, and did not contain polyethersulfone and water. The mass content of water in the core liquid in step one was 60%, the air section temperature in step three was 110°C and the humidity was 85%. The ratio C of the SEM average major diameter of the first hole of the asymmetric sulfonated polyethersulfone hollow ultrafiltration membrane obtained was 3, and the ratio D of the SEM average major diameter of the second hole to the SEM average pore size was 5. Compared with Example 4, the overall flux and mechanical strength of the ultrafiltration membrane of Example 11 were slightly lower, with an overall flux of 71.14LMH / psi and a mechanical strength of 143cN.
[0185] Example 12
[0186] A 100 kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the casting solution in step 1 contained 17 parts by mass of polyethersulfone, 35 parts by mass of water, and a solid content of 14%, the phase separation time in step 3 in the air segment was 3S, and the coagulation bath in step 4 consisted of 98% by mass of water and 2% by mass of Tween 80. The SEM average pore size of the auxiliary retention zone of the finally obtained asymmetric polyethersulfone hollow ultrafiltration membrane was 184 nm, and the SEM average pore size of the steady flow zone was 875 nm. The ratio of the SEM average pore size of the steady flow zone to the SEM average pore size of the auxiliary retention zone was 4.8 times. Compared with Example 4, the initial yield of the ultrafiltration membrane prepared in Example 12 for the insulin refolding solution 30 kD and the mechanical strength of the entire membrane were slightly lower, and the initial yield of the insulin refolding solution 30 kD was 96%, and the mechanical strength of the entire membrane was 159 cN.
[0187] Comparative Example 1
[0188] A 100kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the air segment pre-phase separation in step three was omitted, the coagulation bath temperature in step four was 40°C, and the coagulation bath consisted of 35% by mass of water and 65% by mass of dimethylformamide. The finally obtained asymmetric polyethersulfone hollow ultrafiltration membrane did not contain an auxiliary retention zone, and the pore size of the membrane pores gradually increased from the first surface to the second surface. Compared with Example 4, the ultrafiltration membrane prepared in Comparative Example 1 did not have an area for further retaining impurity molecules, so that the retention efficiency of the membrane for dextran 500kD was 70%, which was not practical.
[0189] Comparative Example 2
[0190] A 100kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared by referring to the preparation method of Example 4, except that the casting solution in step one contained 12 parts by mass of polyethersulfone and 15 parts by mass of water, the coagulation bath in step four consisted of 90% by mass of water, 9.8% by mass of dimethylformamide and 0.2% by mass of Tween 80, and the temperature of the coagulation bath was 80°C. The final asymmetric polyethersulfone hollow ultrafiltration membrane had cracks in the scanning electron microscope image at a magnification of 60×. Compared with Example 4, the ultrafiltration membrane prepared in Comparative Example 2 had a relatively large change in the flow rate inside the membrane, and it caused more damage to the 30kD insulin refolding solution. The yield of the target substance was 75%, which was not practical.
[0191] Comparative Example 3
[0192] A 100 kD asymmetric polyethersulfone hollow ultrafiltration membrane was prepared according to the preparation method of Example 4, except that the casting solution in step 1 contained 35 parts by mass of polyethersulfone, did not contain water, and had a solid content of 35%. The pre-phase separation time in the air section of step 3 was 10 s, and the coagulation bath in step 4 consisted of 60% by mass of water, 32% by mass of dimethylformamide, and 8% by mass of Tween 80. The temperature of the coagulation bath was 100 ° C. The first pore of the asymmetric polyethersulfone hollow ultrafiltration membrane finally obtained was 1.5 pores. The SEM average pore size is 109nm, the SEM average pore size of the auxiliary retention zone is 134nm, and the ratio of the SEM average pore size of the auxiliary retention zone to the SEM average pore size of the first hole is 1.2, indicating that the SEM average pore size of the auxiliary retention zone is slightly larger than the SEM average pore size of the first hole. Compared with Example 4, the ultrafiltration membrane prepared in Comparative Example 3 can better retain impurity molecules, but the overall flux of the membrane is very low, which is 21.45LMH / psi, and is not practical.
[0193] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An asymmetric sulfone polymer hollow ultrafiltration membrane, comprising a main body, one side of the main body is a first surface facing an inner cavity, the other side of the main body is a second surface, and the main body has a non-directional tortuous passage, characterized in that: The first surface comprises a plurality of first holes, and the average pore size of the first holes measured by SEM is 1 nm-450 nm; The ultrafiltration membrane is a membrane with a gradient pore size. And in the thickness direction from the first surface to the second surface, the average pore size of the body first increases, then decreases, and then increases; The main body includes an auxiliary interception area, and the closest average distance A between the auxiliary interception area and the first surface is not less than 40 μm; The ratio of the SEM average pore size of the auxiliary interception zone to the SEM average pore size of the first hole is 1.5-10; The overall porosity of the ultrafiltration membrane is 30%-75%.
2. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 1, characterized in that: The SEM average pore size of the auxiliary interception zone is 10nm-500nm; The average closest distance A from the auxiliary trapping area to the first surface is 50 μm-180 μm.
3. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 1, characterized in that: The pore area ratio of the first surface is 2%-30%, and the initial water contact angle is 50°-85°.
4. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 1, characterized in that: The thickness of the auxiliary interception zone is 3 μm-20 μm; and / or, The thickness of the auxiliary interception zone is 3%-15% of the overall thickness of the membrane; and / or, The closest average distance B from the auxiliary trapping area to the second surface is no greater than 15 μm.
5. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 1, characterized in that: The auxiliary retention zone also includes retention fibers that form a porous structure of the auxiliary retention zone, and the SEM average diameter of the retention fibers is 30nm-90nm; The overall porosity of the ultrafiltration membrane is 35%-70%.
6. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 1, characterized in that: The ultrafiltration membrane comprises a separation zone, the separation zone comprises a first surface, and the thickness of the separation zone is 0.5 μm-5 μm; The ratio of the thickness of the separation zone to the thickness of the auxiliary interception zone is 0.1-0.3; and / or, The ratio of the SEM average pore size of the auxiliary interception zone to the SEM average pore size of the first pores is 1.8-8.
7. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 3, characterized in that: The second surface comprises a plurality of second holes, and the ratio of the SEM average pore size of the second holes to the SEM average pore size of the first holes is 4-15; The hole area ratio of the second surface is 8%-35%, and the hole area ratio of the second surface is greater than the hole area ratio of the first surface.
8. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 7, characterized in that: The first hole is an elliptical structure, the long diameter direction of the first hole is parallel to the length direction of the ultrafiltration membrane, and the ratio C of the SEM average long diameter of the first hole to the SEM average pore diameter is 4-20; The second hole is an elliptical structure, the long diameter direction of the second hole is parallel to the length direction of the ultrafiltration membrane, and the ratio D of the SEM average long diameter of the second hole to the SEM average pore diameter is not greater than 5; And the ratio of the C to the D is 1.5-7.
9. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 1, characterized in that: The area between the second surface and the auxiliary interception area is a steady flow area, and the thickness of the steady flow area is 1 μm-15 μm; The ratio of the SEM average pore size of the steady flow zone to the SEM average pore size of the auxiliary interception zone is 1.2-4; and / or, The flow stabilizing zone further comprises flow stabilizing fibers forming a porous structure of the flow stabilizing zone, and the ratio of the SEM average diameter of the flow stabilizing fibers to the SEM average diameter of the retained fibers is 1.1-2.
10. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 9, characterized in that: The thickness of the steady flow zone is 0.05-0.12 of the overall thickness of the membrane; The SEM average pore size of the steady flow zone is 40nm-1000nm; and / or, The SEM average diameter of the flow-stabilizing fiber is 40nm-100nm.
11. The asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 1, characterized in that: The tensile strength of the ultrafiltration membrane is not less than 120 cN; The thickness of the ultrafiltration membrane is 90 μm-200 μm; The implosion pressure of the ultrafiltration membrane is greater than 0.2 MPa; The initial yield of the ultrafiltration membrane for the target substance is more than 90%; and / or, The yield of the target substance of the ultrafiltration membrane after 10 complete uses is more than 80% of the initial yield.
12. A method for preparing an asymmetric sulfone polymer hollow ultrafiltration membrane according to any one of claims 1 to 11, characterized in that: The steps include: Step 1: Prepare casting liquid and core liquid: The casting solution comprises 15-30 parts by weight of a sulfone polymer, 40-60 parts by weight of a first organic solvent, 15-25 parts by weight of a hydrophilic additive, and 20-40 parts by weight of a non-solvent additive; The core liquid comprises a second organic solvent and water, wherein the mass content of water in the core liquid is 60%-100%; Step 2: Spinning: Extruding the casting solution and the core solution obtained in step 1 from a spinneret together to form a molded product having a first surface and a second surface; Step 3: Pre-phase separation: The molded product obtained in step 2 is pre-phased in an air section to form a green film I, wherein the relative humidity of the air section is 60%-100%, and the pre-phase separation time is 1.5s-3s; Step 4: Complete phase separation: immersing the raw film I obtained in step 3 into a coagulation bath for complete phase separation to obtain raw film II, wherein the coagulation bath is composed of a third organic solvent, water and a surfactant, and the mass content of the surfactant is 0.5%-5% of the coagulation bath solvent; The mass content of water in the coagulation bath is not less than 30%; the complete phase separation time is 50s-150s; Step 5: Cleaning and drying: The raw membrane II obtained in step 4 is cleaned with pure water and then dried to obtain an asymmetric sulfone polymer hollow ultrafiltration membrane; The sulfone polymer is at least one of bisphenol A polysulfone, polyethersulfone, polyphenylsulfone and sulfonated polyethersulfone; The first organic solvent, the second organic solvent and the third organic solvent are at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; The hydrophilic additive is at least one of polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polyethylene imine; The non-solvent additive is at least one of water, isopropanol, glycerol and butanediol; The surfactant is at least one of Tween 80, Tween 20, sodium dodecyl sulfate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and poloxamer.
13. The method for preparing an asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 12, characterized in that: The solid content of the casting solution is not less than 20%; In the step 1, the mass ratio between the non-solvent additive and the first organic solvent is 0.4-0.8; and / or, In the step 1, the mass ratio of the hydrophilic additive to the casting solution is 0.1-0.2, and the ratio of the sum of the mass of the hydrophilic additive and the non-solvent to the mass of the casting solution is not greater than 0.
5.
14. The method for preparing an asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 12, characterized in that: The temperature of the coagulation bath in step 4 is 20-60°C, and the pre-phase separation temperature in step 3 is at least 20°C higher than the temperature of the coagulation bath; and / or, The ratio of the complete phase separation time in step 4 to the pre-phase separation time in step 3 is 35-80; and / or, The running speed of the membrane in step three and step four is 1 m / min-10 m / min.
15. The method for preparing an asymmetric sulfone polymer hollow ultrafiltration membrane according to claim 14, characterized in that: The air bath temperature in step 3 is 50-95° C.; and / or, In the step 2, the temperature of the casting solution is 10-40° C., and the temperature of the casting solution is at least 5° C. lower than the temperature of the coagulation bath.
16. Use of the asymmetric sulfone polymer hollow ultrafiltration membrane according to any one of claims 1 to 11, characterized in that: The ultrafiltration membrane is used for: (a) Removal of endotoxins from raw materials of chemical drugs; (b) Removal of endotoxins from raw materials of traditional Chinese medicine preparations; (c) Removal of macromolecular impurities in insulin intermediates; (d) Collection of recombinant proteins from cell debris / colon homogenate; (e) extracting and purifying proteins and enzymes from fermentation broth; (f) extracting virus particles from cell culture medium; (g) extracting and purifying nucleic acids from cell lysates; (h) Monoclonal antibodies are extracted from hybridoma cell culture medium.
Citation Information
Patent Citations
Highly asymmetric polyethersulfone filtration membranes
US5886059A
Polyether sulfone hollow fiber ultrafiltration membrane and processing device and preparation method thereof
CN106621866A
Hollow fiber membrane module for tangential flow filtration of biomacromolecules and application of hollow fiber membrane module
CN114452823A
PES (Polyether Sulfonate) hollow fiber membrane for biomacromolecule purification as well as preparation method and application of PES hollow fiber membrane
CN114452844A
Multi-region microfiltration membrane as well as preparation method and application thereof
CN118320645A
Cited By
Hollow fiber membrane and preparation method thereof
CN121103155A